What factors enable or limit the role of intermediaries in strengthening transformative capacities? Case studies of intermediaries in two Cambodian cities - Fiona Nicole Lord; Jason Prior; Monique Retamal (Urban Transformations)
Abstract Urban transformative capacities can be strengthened through the role of intermediaries, who are individuals or organisations that work between agencies and identify ways to form coalitions and broker knowledge, drive reforms across scales, and address power disparities. There is limited research to date to understand the factors that enable or limit the role of intermediaries in urban sustainability transformations. Through comparing the roles of intermediaries and their evolution in two case studies cities of urban Cambodia – Battambang and Sihanoukville – through the lens of the urban transformative capacities’ framework of Wolfram (Cities 51: 121–130, 2016), we have identified key factors that impact the effectiveness of these intermediaries. Through qualitative interviews and focus groups, we have found that long-term, place-based, and networked engagement, with political trust and support, is important, alongside the need to demonstrate results and build momentum for transformation through pilots and collaboration. Underpinning these factors are the local power dynamics and structural conditions, as well as the capabilities and attributes of the intermediary actors.